Merging 3D-printing technology and disposable materials for electrochemical purposes: A sustainable alternative to ensure greener electroanalysis - Roveda, Liriana Mara; Ottoni, Vitor Ferreira; de Carvalho, Cláudio Teodoro; Rodrigues, Raphael; Corazza, Marcela Zanetti; Trindade, Magno Aparecido Gonçalves [UNESP] (Elsevier, 2024)
3D-printing technology has revolutionized electrochemical applications by enabling rapid prototyping of various devices with high precision, even in highly complex structures. However, a significant challenge remains in developing less costly and more sustainable analytical approaches and methods aimed at mitigating the negative environmental impacts of chemical analysis procedures. In this study, we propose a solution to these challenges by creating a simple and versatile electrochemical system that combines 3D-printing technology with recyclable disposable materials, such as graphite from an exhausted battery and a stainless-steel screw. Our results demonstrate a novel strategy for developing electrodes and other laboratory-made devices that align with the principles of sustainability and green chemistry. Furthermore, we provide evidence of the effectiveness of the proposed system in an analytical application involving the simultaneous determination of tert-butylhydroquinone, acetaminophen, and levofloxacin using the voltammetric technique in lake and groundwater samples. The results indicate sufficient accuracy, with recovery values ranging from 91 to 110%. Additionally, we utilized the Analytical GREEnness calculator as a metric system to evaluate the environmental friendliness of the proposed electroanalytical protocol. The final score confirms a favorable level of sustainability, reaffirming the eco-friendly nature of our approach.
Keywords: Eco-friendly electroanalysis; Environmental; Green analysis; Lab-made devices; Sustainable development